2020
DOI: 10.1177/1069072720961542
|View full text |Cite
|
Sign up to set email alerts
|

Context and Validation of the Subjective Underemployment Scale Among Turkish Employees

Abstract: The purpose of the current study was to validate the Turkish version of the Subjective Underemployment Scales (SUS; Allan et al., 2017), a recently developed measure aimed at assessing the six components of underemployment: pay, status, field, hours, involuntary temporary work, and poverty wage employment. The proposed six-factor structure of the SUS was empirically supported among a diverse group of Turkish employees (211 female, 190 male with a mean age of 32.31; ranging from 20 to 63). Consistent with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Our central finding was that participants whose skills exceeded the requirements of the experimental task experienced greater POQ, which in turn decreased task meaningfulness. This aligns with previous research suggesting that basic or rote tasks relate to greater POQ (Lobene et al, 2015) and extends other cross-sectional studies finding that POQ is negatively associated with meaningful work (Allan et al, 2017; Buyukgoze-Kavas et al, 2020). In addition, the finding that POQ operated as a mediator supports the contention that POQ mediates objective overqualification and other outcomes; in other words, workers experience poorer outcomes only when they subjectively interpret themselves as overqualified (Lobene et al, 2015; Liu & Wang, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Our central finding was that participants whose skills exceeded the requirements of the experimental task experienced greater POQ, which in turn decreased task meaningfulness. This aligns with previous research suggesting that basic or rote tasks relate to greater POQ (Lobene et al, 2015) and extends other cross-sectional studies finding that POQ is negatively associated with meaningful work (Allan et al, 2017; Buyukgoze-Kavas et al, 2020). In addition, the finding that POQ operated as a mediator supports the contention that POQ mediates objective overqualification and other outcomes; in other words, workers experience poorer outcomes only when they subjectively interpret themselves as overqualified (Lobene et al, 2015; Liu & Wang, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, researchers found that subdimensions of the scale scores ranged from 0.95 to 0.97. The Turkish version of the SUS indicated good internal consistency between 0.87 and 0.96 [60]. In the current study, the internal consistency reliabilities for subdimensions of the scale ranged from 0.85 to 0.96.…”
Section: Instruments 211 Underemploymentmentioning
confidence: 47%